The dynamics of ice melting in the conditions of crybot movement; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Zakharova E. Ekaterina (2017, 2017)
Title screen